Cognitive enhancers - what we should know about them - Andrzej Stańczak; Wiesaława Lewgowd (Polish Pharmaceutical Society, 2021)
Nootropics also called smart drugs, memory enhancers, neuroenhancers, cognitive enhancers, are a chemically and pharmacologically heterogeneous group of medicines and active sub-stances that improve mental functions such as memory, intelligence, motivation, attention, and concentration. They are used to treat cognition deficits in patients suffering from dementia, schizophrenia, stroke, Alzheimer's disease, Parkinson's disease, Huntington's disease, and ADHD. According to the definition, which was proposed by a Romanian psychologist and chemist Corneliu E. Giurgea nootropics should be characterized by the ability to cross the blood-brain barrier, lack of typical pharmacological effects of psychotropic medicines, a small number of reported side effects, and extremely low toxicity. Their pharmacological activity depends on various mechanisms of action. They stimulate the metabolism of nerve cells and increase their resistance to hypoxia, regulate cerebral circulation, as well as exhibit anticoagu-lant/antiplatelet and neuroprotective properties. In addition, these compounds directly or indi-rectly increase the concentration of neurotransmitters essential for appropriate brain function-ing such as acetylcholine, dopamine, and glutamate. Therefore, procognitive medicines which increase cholinergic transmission are used in the symptomatic treatment of mild to moderate dementia associated with Alzheimer's disease. Collaterally to synthetic nootropics, there is also a group of natural plant substances that have proven the ability to improve brain function. They have a beneficial effect on cognitive functions such as learning ability, memory, concen-tration and exhibit neuroprotective action. Natural nootropics also slow down the aging pro-cesses, progressing with age and intensifying cognition deficits. But nowadays, medicines that help people with neurological and psychiatric conditions are used by healthy individuals as brain boosters because they increase concentration level, motivation, memory functions, and efficiency while reducing sleep time without feeling tired. Therefore they are willingly taken by students and people working in highly competitive industries. There is a number of natural and synthetic brain boosters available, but some of them exhibit a lot of side effects.